2018
DOI: 10.1590/s1980-220x2017047903382
|View full text |Cite
|
Sign up to set email alerts
|

Development of a virtual simulation game on basic life support

Abstract: Objective: To validate the content of a virtual learning object in the format of a Role Playing Game - educational simulation game about basic life support, aimed at academics and health professionals. Method: Methodological, construction and validation study with qualitative data approach on the content of a virtual learning object, conducted between August and September 2016. Results: The game was developed in 13 screens, of which nine presented contents of basic life support, and the others presented g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
0
9
0
12
Order By: Relevance
“…Although past studies have found that AV feedback can improve CPR quality (18), the additional application of the AR technology to overlay a holographic image of the circulatory system, which is responsive to the quality of CPR being performed, is novel. While studies have found that using immersive technologies similar to AR, such as virtual reality, can improve trainee experience and confidence, to our knowledge, no studies have linked these technologies with outcomes (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although past studies have found that AV feedback can improve CPR quality (18), the additional application of the AR technology to overlay a holographic image of the circulatory system, which is responsive to the quality of CPR being performed, is novel. While studies have found that using immersive technologies similar to AR, such as virtual reality, can improve trainee experience and confidence, to our knowledge, no studies have linked these technologies with outcomes (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 96%
“…Though few studies examine the use of AR for resuscitation simulation, a larger body of evidence exists using virtual reality (VR) for CPR training, as well as for observation of bystander response metrics, and other resuscitation skills (20,22,(27)(28)(29)(30)(31)(32). Due to the considerable difference in VR from AR, whereas in the VR environment a user cannot see or interact with the real environment, comparing studies using VR may not be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…A titulação dos juízes, experiência profissional e publicação sobre o tema são aspectos relevantes para a qualidade da avaliação e do produto da validação como apontado em estudos de validação (COSTA et al, 2018a;GOMES et al, 2018).…”
Section: )unclassified
“…(33,33%) itens do REO foram acatadas para os itens com PC menor que 80%. O trabalho de validação é elemento substancial do processo de ensinoaprendizagem de um projeto de EAD e confere confiabilidade e qualidade ao conteúdo (COSTA et al, 2018a;GOMES et al, 2018).…”
Section: )unclassified
See 1 more Smart Citation